An empirical analysis of EFL teachers digital literacy in Chinese higher education institutions - Lei Feng; Piyapong Sumettikoon (My University, 2024)
Abstract In 2022, China’s Educational Ministry, for the first time, released an industry standard for teachers’ digital literacy. This standard provides a holistic framework for teachers’ digital literacy (TDL) in five dimensions. Since few studies have investigated EFL teachers’ digital literacy, the relationships among the five dimensions proposed for EFL teachers’ digital literacy remain unknown. Therefore, this research applied a quantitative method using a five-point Likert questionnaire designed based on TDL. Ninety-two EFL teachers from two universities and one higher vocational college in China participated in this questionnaire research. Partial least squares structural equation modeling was used to assess the relationships between these five dimensions. The relationships between the five TDL dimensions were highlighted by the findings, which supported the proposed model. In addition, implications for enhancing EFL teachers’ future digital literacy have been provided to facilitate and favor EFL teachers’ digital literacy development.
Keywords: Empirical Research; Digital Literacy; Digital literacy in education